Indicators of immune activation in major depression - Sluzewska, Anna; Rybakowski, Janusz; Bosmans, Eugene; Sobieska, Magdalena; Berghmans, Robert; Maes, Michael; Wiktorowicz, Krzysztof (Psychiatry research, 1996)
Immune-inflammatory markers and their correlations were examined in patients with major depression. Plasma concentrations of interleukin-6 (IL-6), soluble IL-6 receptor (sIL-6R), soluble interleukin-2 receptor (sIL-2R), transferrin receptor (TfR), C-reactive protein (CRP), and α 1-acid glycoprotein (AGP), as well as the microheterogeneity of AGP, were measured in 49 major depressed patients during an acute phase of the illness and compared with concentrations in 15 normal control subjects. Plasma concentrations of IL-6, sIL-6, sIL-2R, TfR, CRP, and AGP were significantly higher in major depressed patients than in healthy control subjects. Patients with higher values of AGP microheterogeneity coefficient (AGP-RC > 1.5) had significantly higher concentrations of AGP, IL-6, and TfR. The correlations between cytokines and acute phase proteins studied point to a significant role of elevated IL-6 secretion in the induction of Type I AGP microheterogeneity changes that are characteristic of some inflammatory conditions.